Vocational high school students’ chemical literacy on context-based learning: A case of petroleum topic - Wıyarsı, Antuni; Pratomo, Heru; Prıyambodo, Erfan (Journal of Turkish Science Education, 2020)
The study aims to investigate the effect of context-based learning (CBL) on vocational high school students’ chemical literacy of petroleum topics. Through quasi-experimental research with pretest-posttest design, 30 students from the automotive engineering program were assigned as the experimental group, while 31 students from the same school were devoted to the control group. The experimental group was exposed to the CBL whereas the control group was taught with traditional learning. To collect data, a petroleum chemical literacy test (PCLT) with 8 open-ended questions was used. The data were analyzed via Independent t-test and descriptive analysis. The results showed a statistically significant difference between the chemical literacy levels of the experimental and control groups. Even though the students have good chemical literacy in implementing the CBL, they need to improve their abilities to reach the goals of the science/chemistry curriculum. The current study suggests that the CBL should be further used in vocational high school to enhance students' chemistry achievements.